2007
DOI: 10.1111/j.1574-6941.2007.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the dynamics of initial bacterial colonization of nonconserved forage in the bovine rumen

Abstract: Microbial colonization is central to ruminal degradation of dietary material yet little is known about the dynamics of this process. The aim of this study was to characterize the initial stages of bacterial colonization of forage, and to assess the impact that different postsample processing and analysis methods had on the results obtained. Bacterial 16S rRNA gene-based analysis of damaged, nonconserved perennial ryegrass, incubated in sacco in the bovine rumen, required the development and validation of new q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 55 publications
2
59
0
Order By: Relevance
“…Furthermore, the functional hierarchical classification was illustrated by using SEED subsystem. The sequences were compared using the BLASTX algorithm with an expected cut off of 1 × 10 −5 [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the functional hierarchical classification was illustrated by using SEED subsystem. The sequences were compared using the BLASTX algorithm with an expected cut off of 1 × 10 −5 [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown temporal changes in bacterial (Edwards et al, 2007; Huws et al, 2013) and fungal (Edwards et al, 2008) populations during ruminal incubation of fresh perennial rye grass ( Lolium perenne ). Specifically, these studies revealed a rapid colonization of the plant material within 5 min of rumen-incubation by both bacterial (Edwards et al, 2007) and fungal populations, followed by a compositional shift in bacterial populations between 2 and 4 h following incubation (Huws et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown temporal changes in bacterial (Edwards et al, 2007; Huws et al, 2013) and fungal (Edwards et al, 2008) populations during ruminal incubation of fresh perennial rye grass ( Lolium perenne ). Specifically, these studies revealed a rapid colonization of the plant material within 5 min of rumen-incubation by both bacterial (Edwards et al, 2007) and fungal populations, followed by a compositional shift in bacterial populations between 2 and 4 h following incubation (Huws et al, 2013). Compositional dynamics may vary among forage types based on observed differences in fiber disappearance and fibrolytic enzyme activities (Bowman and Firkins, 1993) and the observed temporal changes in microbiota may be affected by residual plant metabolism of fresh forages (Huws et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In present study, 16S rRNA genes were amplified from plant material and the choice of primer was made to avoid amplification of chloroplast 16S rRNA gene 23,24 . There are a wide variety of other primers available that vary in term of the product length, taxonomic power and usefulness 25,26 .…”
Section: Discussionmentioning
confidence: 99%